Differential response of IVP, parthenogenetic and nuclear transfer derived bovine embryos upon environmental heat stress-implications for expression of autosomal and X-linked genes - Hashem, MA; Hossain, MM; Mohammadi-Sangcheshmeh, A; Cinar, U; Rings, F; Schellander, K; Tesfaye, D; Hoelker, M (Bangladesh Journal of Animal Science, 2013)
The present study was conducted to examine the metabolic activities and expression differences of X-linked and autosomal genes upon exposure to heat stress using different types of bovine embryos. Embryos from in vitro fertilized (IVF), parthenogenetic (PA) and nuclear transfer (NT) were given heat treatment at morula stages at 40°C for 6 hrs. Treated embryos were studied for metabolic activities by quantification of G6PD-activity through Brilliant Cresyl Blue (BCB) staining and were used for X-linked and autosomal gene expression studies. Quantification of G6PD, PGK1, XIST as sex linked and SOX, BAX, OCT4, HSP70.1 as autosomal genes and GAPDH (endogenous control) mRNAs in each cDNA sample from heat treated and untreated embryos were assessed by quantitative PCR. Results of the present study indicate sexually dimorphic expression of selected X-linked and autosomal genes upon exposure to heat stress at morula stage in IVF, PA and NT embryos. Moreover, our study showed that female IVP derived embryos show highly decreased levels of XIST after heat shock. That could be one of the reasons for reduced in vitro developmental competence of female bovine embryos since XIST is the responsible gene for X-chromosome inactivation. Any disturbance would result in dysregulation of all X-Chromosomal encoded genes. DOI: http://dx.doi.org/10.3329/bjas.v42i1.15759 Bang. J. Anim. Sci. 2013. 42 (1): 1-10